1991
DOI: 10.1002/hed.2880130410
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of expanded tissue

Abstract: The relatively recent advent of tissue expansion for medical purposes precludes the availability of extensive knowledge concerning the physiologic and histologic changes that occur during controlled expansion of the skin. This paper reviews the basic science and clinical research that has been conducted to investigate the changes and summarizes the findings. It can be concluded that flaps harvested from skin previously expanded have an improved survival rate compared to similar flaps developed in nonexpanded s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Furthermore, it has been well documented in histologic examination of tissue-expanded skin specimens that expanded dermis is thinner with greater elastosis and zonal fragmentation of elastic fibers. 24,25 Lastly, it has been speculated that the contractile forces arising from the capsule around the breast implant cause further loss of nipple projection in this unique group of patients. 12 Since the original description of the skate nipple reconstruction, there has been little in the literature describing its modern-day modifications.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, it has been well documented in histologic examination of tissue-expanded skin specimens that expanded dermis is thinner with greater elastosis and zonal fragmentation of elastic fibers. 24,25 Lastly, it has been speculated that the contractile forces arising from the capsule around the breast implant cause further loss of nipple projection in this unique group of patients. 12 Since the original description of the skate nipple reconstruction, there has been little in the literature describing its modern-day modifications.…”
Section: Discussionmentioning
confidence: 98%
“…In what follows, we will compare the response of our model to skin growth experiments in the literature [9, 10, 12, 64, 66, 68]. Unfortunately, almost all existing data are based on in vivo tissue expansion studies.…”
Section: Discussionmentioning
confidence: 99%
“…Acutely, tissue expansion has been associated with slight epidermal thickening and significant dermal thinning [9], resulting in an overall thinning and a reduced tensile strength [10]. Mechanically, a study in rodents reported an acute increase in uniaxial stretch of approximately 36% [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations